Hosts' Perception of Economic and Socio-Cultural Tourism Impacts - Anton Ogorelc; David Kamšek; Borut Milfelner (Naše gospodarstvo/Our economy, 2013)
Analyzing tourism perceptions of host communities and residents’ attitudes toward tourism development has been gaining increasing attention in the tourism research. This paper examines how residents perceive positive and negative economic and socio-cultural impacts of tourism. The authors identify several differences betwe- en two groups of respondents: residents employed in tourism and other residents. The study provides tourism planners with useful information concerning specific ele- ments associated with residents’ positive and negative perception of the impact of tourism.